Apostolic Succession - Hall, Noel (Scottish journal of theology, 1958)
The renewed emphasis on the doctrine of apostolic succession which was the outcome of the Oxford Movement in the Church of England is an example of the power inherent in dogmas to recover their vitality. This is no isolated phenomenon confined exclusively to the dogmas of the Christian faith; in our own times we have witnessed the far-reaching results of the revival of the Marxian dogma of dialectical materialism in the sphere of international politics. That bishops are the successors of the Apostles was a belief held without question by the majority of Anglican Churchmen at the dawn of the nineteenth century, but it cannot be contended that they were fully alive to its implications. The awakening came through the publication of the Tracts for the Times. The challenge was sounded with unambiguous clarity in the very first of them to issue from the press. ‘Now then, ’ wrote John Henry Newman, ‘let me come at once to the subject which leads me to address you. Should the Government and the country so far forget their God as to cast off the Church, to deprive it of its temporal honours and substance, on what will you rest the claim of respect and attention which you make upon your flocks? Hitherto you have been upheld by your birth, your education, your wealth, your connexions; should these secular advantages cease, on what must Christ's ministers depend?… I fear we have neglected the real ground on which our authority is built: our Apostolic Descent.